Qualitative and quantitative analysis of sildenafil in traditional medicines and dietary supplements - Podder, Ashis Kumar; Chakrobarty, Jayanta Kishor; Faroque, A. B. M. (© 2014 Asian Journal of Pharmaceutical and Clinical Research, 2016)
This article was published in the Asian Journal of Pharmaceutical & Clinical Research [© 2014 Asian Journal of Pharmaceutical & Clinical Research] and the definite version is available at: http://innovareacademics.in/journals/index.php/ajpcr/article/view/987/760